Tata Kelola Keuangan Gereja: Pengabdian Pada Jemaat GSJA Logos Kotaraja Jayapura - Iek, Mesak; Sowe, Marthen Luther; Delvi Way, Jems (The Community Engagement Journal, 2025)
Without good and transparent management, a church will have difficulty in developing its service vision. This condition also warned in the service at GSJA Logos Kotaraja. In order to improve modern service and win many souls to come to God, it is necessary to carry out socialization activities on Church Financial Management Governance in the GSJA Logos Kotaraja Congregation. From the results of the socialization, it can be concluded that: (1) Without good and transparent management, a church will have difficulty in developing its service function optimally. (2) Good church financial governance is very important because it is the basis for effective and sustainable financial management and can encourage the achievement of: (a) financial stability, (b) preventing waste, and (c) achieving good financial goals in the short and long term. (3) GSJA Logos has not yet established an internal audit team and the administrative process has not been optimally organized. (4) This socialization has printed a standard operating procedure (SOP) book for financial management for congregation treasurers and department treasurers as a guide in managing finances to support church services starting from services in the congregation as well as services in each department. Keywords: governance, financial, church